RET : Network for the understanding of the territory. The case of Buenos Aires, Argentina - Bozzano, Horacio (2007)
The RET "Red para el Entendimiento Territorial" is the Network for the Understanding of the Territory of the Province of Buenos Aires,in the Republic of Argentina. At present the RET is in the instance of formation of a Partnership in which participate: the UTN (National University of Technology), the Zanetta Foundation, the Government of the Province of Buenos Aires, which is now working to contribute to the UJFK (University John F.Kennedy), the UNLP (National University of La Plata), the CONICET, (National Board of Scientific and Technological Investigation) and differents Municipalities. The methodology is organized around three key questions: 1- why a network?, 2-why territorial understanding? and 3 - why real, legal and thought territories? The project is developed from a sense of the communication related to theories that put emphasis in the intersubjective processes and the cultural processes. Among other activities, at present the RET: a) publishes georeferenced territorial information per rural allotment and blocks referred to theoretical use (urban codes) and real use of the ground for 134 Municipalities of the Province; y b) it does research about legal, real and thought territories. The publication is organized as follows: 1-methodological criteria; 2- antecedents and beginning; 3-conception of the RET; 4-theoretical concept of territory, place and management; 5-territorial concepts and axis analysis; 6-Real territories: applied to RET; 7-legal territories: applied to RET; 8-thought territories: applied to RET; 9- development of programs and instruments, and 10-institutionalization of the Network. Conclusions are referred to theoretical and epistemologic bases in territorial understanding.